MENINGKATKAN MOTIVASI BELAJAR SISWA MELALUI MEDIA KUBUS BERANAK DALAM PEMBELAJARAN MATEMATIKA - Dike Rinanda Irfi'ani; Wuli Oktiningrum (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2020)
The lack of use of instructional media on the volume material for building cubic spaces in mathematics learning for grade 5 elementary schools. This study aimed to improve students' learning motivation on the volume material of cubes through learning media cubes beranak in mathematics learning in grade 5 elementary school. This research procedure used the ADDIE model development design consisting of Analysis, Design, Development, Implementation, and Evaluation. The increasing of students learning motivation before and after using childbirth cube media based on questionnaire. The results of this study showed that the level of validity of this media based on the evaluation of material experts 81,6% with very valid validity criteria, 72,5% media experts with valid validity criteria, 89,3% expert learning implementation plan with very valid validity criteria, Expert Student Worksheet 91,6% with validity criteria very valid. Student responses to child cube media obtained an average value of 81,1% with a very good assessment category, the teacher's response to child cube media obtained a value of 100% with a very good assessment category. Based on the data on student learning motivation before using the media cubes, the average child was 53,61 with the enough category increased to 81,04 with the very high category after using the child cube media